Pengaruh Tingkat Produksi, Konsumsi, dan Harga Kopi terhadap Impor Kopi di Indonesia - SANI, PENINA DOLFINA; USTRIYANA, I NYOMAN GEDE; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Effect of Production Rate, Consumption, and Price to Coffee Imports into Indonesia This research aims to study the effect of coffee production, consumption, and price to import volume of Indonesian coffee from the year 1982 to 2017, whether simultaneous effect or partial effect. Coffee production variable (X 1 ), coffee consumption (X 2 ) and coffee price (X 3 ) are independent variables in this study, with total import of Indonesian coffee (Y) as dependent variable. The study is descriptive, with quantitative approach. Data used in this study include data of Indonesian coffee volume import in the period of 1982 to 2017. Data source gathered from the Central Statistics Agency, and official website of the Agriculture Department. Data analysis used in this study is statistical analysis of multiple linear regression using SPSS. Production, consumption, and the price of coffee in Indonesia have significant effects toward Indonesia’s import of coffee. Coffee production has a significant negative effect on coffee imports. While coffee consumption and coffee price have significant positive effects on coffee import. Coffee consumption in Indonesia is a variable which has a dominant effect towards coffee import. Based on various analysis above, it is recommended for the government to increase domestic coffee production by increasing land productivity, using superior variety, strengthening farmer’s institutional system, as well as improving domestic price policy of coffee.